A new phase efficiency calculation model for optimization of a hat‐fed reflector antenna with arbitrary radius of ring‐shaped phase center. Issue 12 (5th October 2020) - Cai, Ming‐Bo; Yan, Ze‐Hong; Yi, Xiang‐Jie; Yang, Shu‐Yang; Zhang, Zhi‐Ya
Abstract: A hat‐fed reflector antenna with large radius of ring‐shaped phase center (RSPC) is reported in this article. First, a new phase efficiency calculation model (PECM) based on new phase reference point is presented, which can accurately calculate the phase efficiency of a hat‐fed with arbitrary radius of RSPC. Second, based on the invented PECM, the hat‐fed can be optimized by using cosimulation method of HFSS and MATLAB, high aperture efficiencies are achieved in the whole band. To prove the validity of the new PECM, a hat‐fed reflector antenna with large radius of RSPC is designed, manufactured, and measured. The measured results are in good agreement with the simulations. The results show that the developed hat‐fed reflector antenna has achieved a VSWR of less than 1.18, the peak realized gain of 43.5 dBi and an aperture efficiency of higher than 67.4% in the entire band from 12.25 to 14.5 GHz.